Buster Keaton - Silent Classics, 2 - Keaton, Buster; Cline, Edward F.; Lessley, Elgin; Roberts, Joe; Seely, Sybil (starmedia, 2006)
Flitterwochen im Fertighaus (1920): Decades before Jackie Chan, Buster Keaton was famous for his often perilous physical comedy and dangerous stunts. This short film is the one that contains the infamous wall-falling scene, where Buster is saved from certain doom by a well-placed window. There are no stunt doubles, camera tricks, or fancy prop gadgets - the gag happened just as it appears, and had Keaton been standing a few inches the wrong way, the results might have been fatal. [www.rinkworks.com]
Keywords: DVD-Video